SCIENTIFIC SUPPORT OF VEGETABLE, MELON, AND POTATO GROWING IN RUSSIA - I. V. Savchenko; N. I. Bocharnikova (Овощи России, 2015)
The summary report of research investigations of the institutes of the Russian Academy of Agricultural Science, the Russian Academy of Science, and the Institutions of Higher Education in 2013 on the project «Development of new varieties and high-precision sustainable zonal technologies of vegetable and cucurbits crops growing with the use of new varieties and hybrids, high'quality seeds, advanced approaches of agro-techniques, plant protection, and mechanical equipments» is represented.